Intraoperative Soft Tissue Balance/Kinematics and Clinical Evaluation of Modified Kinematically versus Mechanically Aligned Total Knee Arthroplasty - Matsumoto, Tomoyuki; Takayama, Koji; Ishida, Kazunari; Kuroda, Yuichi; Tsubosaka, Masanori; Muratsu, Hirotsugu; Hayashi, Shinya; Hashimoto, Shingo; Matsushita, Takehiko; Niikura, Takahiro; Kuroda, Ryosuke (The Journal of Knee Surgery, 2020)
Recently, kinematically aligned total knee arthroplasty has been found to achieve better clinical outcomes than mechanically aligned TKA. Despite the good clinical outcomes that are reported at short- to mid-term follow-up, intraoperative variables that are associated with a better outcome have not been measured. Therefore, this study was conducted to compare intraoperative kinematics/soft tissue balance and the clinical outcomes of patients who underwent modified kinematically (restricted tibial cut) or mechanically aligned total knee arthroplasty. Sixty cruciate-retaining total knee arthroplasties (30 modified kinematically [3-degree varus and 7-degree posterior slope in tibial cut] and 30 mechanically aligned) were performed in patients with varus-type osteoarthritis using a navigation system. Intraoperative kinematics assessed by the navigation system and soft tissue balance assessed by an offset-type tensor were compared between the groups. One year postoperatively, the range of motion and 2011 Knee Society scores were compared between the groups. Kinematic assessment exhibited that tibial internal rotation during flexion was significantly maintained in the kinematic compared with the mechanical group (p < 0.05). Varus/valgus ligament balance at 90 and 120 degrees of flexion significantly maintained lateral laxity in the kinematic compared with the mechanical group (p < 0.05). Improvement of flexion angles, functional activity scores, and patient satisfaction were significantly better in the kinematic than in the mechanical group (p < 0.05). Modified kinematically aligned cruciate-retaining total knee arthroplasty maintained more tibial internal rotation and lateral laxity during flexion than mechanically aligned total knee arthroplasty; thus, the former may result in better clinical outcomes.
Keywords: total knee arthroplasty; kinematic alignment; mechanical alignment; soft tissue balance; kinematics